Voces entre alambradas: los primeros pasos del exilio español en Francia. Una historia que aún se está escribiendo - Ruiz del Árbol Cana, Antares (Millars. Espai i Història, 2010)
The beginning of the Francoist offensive against Catalonia, in December 1938, caused a widespread movement of people seeking asylum in the neighbour country. Between the months of January and February, nearly 450,000 Spanish refugees had crossed the Pyrenees. From the start, in response to this massive arrival of refugees, the French government promoted their repatriation, through agreements negotiated with the government in Burgos. With a lapse of time of five months between the two wars, the pre-war scenario in France in 1939 generated new demands that affected the perception on the refugees, configuring a permanent exile on both sides of the Atlantic.